SUBSTRATE REMOVAL IN MICROBIAL FILM REACTORS Part I :Mathematical Model - Muslu, Yilmaz (Informa UK Limited, 1993)
ABSTRACT Mass transfer within microbial films is described using Monod type biological kinetics in terms of the properties of packing material and feed solution. A second-order partial differantial equation describing the dispersion phomena inside the liquid layer is solved using an approximation for the concentration gradient. Computer techniques have been developed for the numerical evaluation of the normalized biofilm mathematical model.